Study of Luminescence Properties of PVA Capped Porous Silicon Carbide Microparticles Thin Films Deposited by Spin Coating Method - KACI , Samira (International Journal of Computational and Experimental Science and Engineering, 2017)
In order to be used in an optical device, thin films of pure Poly Vinyl Alcohol and PVA mixed with porous SiC microparticles were prepared by spin coating technique. The average size of SiC microparticles were 7mm. An electroless method was used for producing porous silicon carbide powder under UV irradiation was investigated. The electroless process was chosen because it does not require electrical contact during etching like in anodic one. Silver nanolayer coated SiC particles was formed by polyol process prior the etching and served both as an anode, catalyst and mask for the reduction of a chemical oxidant. The etchant was composed of HF and different oxidants in water. Various porous morphologies are presented and studied as a function of etchant concentration, oxidant type, etching time, and wavelength of irradiation. Morphological, optical and photoluminescence characterizations of SiC micropowder embedded in PVA matrix and deposited as thin films on glass substrates are reported. We concluded that the chemical etching conditions of SiC powder seems to have a large impact on the resulting properties. We noticed that SiC powder etched under UV light of 254 nm using K2S2O8 as oxidant, at reaction temperature of 80°C for t=40min exhibited the best photoluminescence property.